Self Management Menentukan Kualitas Hidup Pasien Diabetes Mellitus - Luthfa, Iskim; Fadhilah, Nurul (Jurnal Endurance, 2019)
People with diabetes mellitus are at risk of developing complications, so that it affects the quality of life. These complications can be minimized through self-care management. This study aims to determine the relationship between self management with the quality of life for people with diabetes mellitus. This research is a kind of quantitative research with correlation study. This research used cross sectional design. The sampling technique uses non probability with estimation consecutive sampling. The number of respondents in this research are 118 respondents. Instrument for measuring self management used diabetes self management questionnaire (DSMQ), and instruments to measure quality of life used quality of life WHOQOL-BREEF. The data obtained were processed statistically by using spearman rank test formula and p value of 0,000 There is a significant relationship of self management with the quality of life of people with diabetes mellitus. Penderita Diabetes mellitus beresiko mengalami komplikasi yang dapat mempengaruhi kualitas hidupnya. Komplikasi tersebut dapat diminimalkan melalui manajemen perawatan diri (self management). Penelitian ini bertujuan untuk menganalisis hubungan self management dengan kualitas hidup pasien diabetes melitus. Jenis penelitian ini adalah deskriptif korelasi dengan desain cross sectional. Teknik pengambilan sampel menggunakan non probability sampling dengan pendekatan consecutive sampling. Jumlah sampel sebanyak 118 responden. Instrumen penelitian untuk mengukur self management menggunakan diabetes self management questionnaire (DSMQ), dan instrumen untuk mengukur kualitas hidup menggunakan quality of life WHOQOL-BREEF. Analisis data menggunakan spearman rank dan didapatkan hasil nilai p value 0,000 dan r 0,394.Terdapat hubungan antara self management dengan kualitas hidup pasien diabetes mellitus dengan arah korelasi positif.